9x-4=7x-1

Simple and best practice solution for 9x-4=7x-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x-4=7x-1 equation:


Simplifying
9x + -4 = 7x + -1

Reorder the terms:
-4 + 9x = 7x + -1

Reorder the terms:
-4 + 9x = -1 + 7x

Solving
-4 + 9x = -1 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
-4 + 9x + -7x = -1 + 7x + -7x

Combine like terms: 9x + -7x = 2x
-4 + 2x = -1 + 7x + -7x

Combine like terms: 7x + -7x = 0
-4 + 2x = -1 + 0
-4 + 2x = -1

Add '4' to each side of the equation.
-4 + 4 + 2x = -1 + 4

Combine like terms: -4 + 4 = 0
0 + 2x = -1 + 4
2x = -1 + 4

Combine like terms: -1 + 4 = 3
2x = 3

Divide each side by '2'.
x = 1.5

Simplifying
x = 1.5

See similar equations:

| 9x-4+7x-1= | | E=ex | | k^2+4k+4=-7 | | 5(a-4)=6(a-7) | | -[8x+(3x+8)]=1-(3x+3) | | -0.64-6.7u=-6.7u | | 8-3[5-(4y-8)]=0 | | -13+2r+2-r=1+4r | | x^5+3x^4-3x^3-x^2-3x+3=0 | | 17p-1=3p+12+14p | | 10a-45=3(a-15) | | x+92=-47 | | -4(1-4v)-6=-32+5v | | -2+4z=4z-2 | | 10a-45=3a-45 | | 2r+1=4r-1 | | x-3=-40 | | 8(c-3)=5c+24 | | 79+x=94 | | 3x-4(2x-9)=5x+11 | | w=100/4 | | -19.55-6.6j=-19.3j+17.1j+18.73 | | (-51)+x=38 | | 6x+4x=18 | | 8h-11(h+4)=-77 | | 7x+4x=-x | | 1108473/4=x | | 7(z+11)=4(z+11) | | 3X^2-20x+15=0 | | -15+16+19d=20+19d | | 12(2x-9)=4(6x+6) | | 6x-17=4x+31 |

Equations solver categories